If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1g + 2(3 + 9) = 4(g + 1) Combine like terms: 3 + 9 = 12 -1g + 2(12) = 4(g + 1) Multiply 2 * 12 -1g + 24 = 4(g + 1) Reorder the terms: 24 + -1g = 4(g + 1) Reorder the terms: 24 + -1g = 4(1 + g) 24 + -1g = (1 * 4 + g * 4) 24 + -1g = (4 + 4g) Solving 24 + -1g = 4 + 4g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4g' to each side of the equation. 24 + -1g + -4g = 4 + 4g + -4g Combine like terms: -1g + -4g = -5g 24 + -5g = 4 + 4g + -4g Combine like terms: 4g + -4g = 0 24 + -5g = 4 + 0 24 + -5g = 4 Add '-24' to each side of the equation. 24 + -24 + -5g = 4 + -24 Combine like terms: 24 + -24 = 0 0 + -5g = 4 + -24 -5g = 4 + -24 Combine like terms: 4 + -24 = -20 -5g = -20 Divide each side by '-5'. g = 4 Simplifying g = 4
| 4/5n-k/5n | | f(x)=2x^3-4x^2-10x+20 | | 3(w+2w)+(5-2)*4+14w= | | 6+-3y-6y=-15 | | 0.2(600-2.4x)=3.7(3x-3000) | | -22/35*(-15/-33) | | (w-6)(8w+9)=0 | | 30x+20=36+28x | | 5,880/3000 | | 11.1x+1.2x-5.4=-10 | | -22/35*-15/-33 | | 0.2(600-2.4x)=3.7(6000) | | (2x+10)(6x-10)= | | -8=8-6n-4 | | 3x-8x-2y+6= | | 2-y-7= | | c^2-3c=14+2c | | 6.4x-3.9(x-1)=7.1 | | (r+9)(r-1)=0 | | -2=8+2x | | 1x+34=3x | | r^2+2r-85=-3 | | 1x+13=135 | | 3x-4(2)+6=0 | | 0.5z+8.6=4.8z | | 72/32 | | 13.7y=6.2+30 | | 0.5z+8.6z=4.8z | | 0.007x+0.03=0.01 | | 3/4x-2-4(1/2x-2) | | -5x^2-16=x-2-8x^2 | | 7[1-(3c+9-2c-6)]=-14c |